Effect of selective laser melting process parameters on properties of 316L stainless steel - Nurul Kamariah, Md Saiful Islam (2020)
Selective laser melting (SLM) is capable of producing metallic components with comparable properties as bulk material. Anisotropic properties, process parameters and notable interfacial stresses influence the final properties of a final fabricated component. This research concerns about the effect SLM process parameters –low value of energy density and design of building directions; as well as heat treatments on the properties of fabricated SLM-ed 316L stainless steel. This research investigate the effects of different energy densities (60 and 65 J/mm3) and building orientations of 0°, 45° and 90° on the physical and mechanical properties; as well as effects on heat treatment temperatures (650, 950 and 1100 °C) on mechanical properties and corrosion behaviour of 316L stainless steel samples fabricated by SLM. The dimensional accuracy and relative density decrease with the decrease of energy densities and building orientations. Significant deformation is observed for 0 build orientation which contributes the lowest relative density of 0 build orientation compares to 45° and 90° build orientations. However, high relative densities (98-99.2%) are achieved for all asbuilt samples condition. The amount and size of porosity are aligned with the relative density. Reduction of hardness and strength of the low energy density (60J/mm3) samples are associated with the highest amount of porosity. For building orientation, hardness and strength of as-built SLM-ed 316L stainless steel samples are influenced by the combination of pores and high residual stress. Types of molten pool boundaries (MPBs) slipping in the microstructure features varies with the inclination building orientations and may significantly affect the ductility. High elongation at fracture from around 40% to 85% was reached after the heat treatment at 950ºC and above for Low energy density (60 J/mm3) of SLM-ed 316L stainless steel samples. In addition, the hardness, yield strength and ultimate tensile strength declined after heat treatment due to a decrease in dislocation density, compress stress relief, and an increase in number and size of small pits-like features. The increased heat treatment temperatures cause a slight reduction of corrosion potential influenced by porosity, dislocation density and residual stress. The outcomes of building orientation and energy density show that asbuilt samples built up 0º BO and 90º BO at high energy density (65J/mm3) have the overall highest product quality. Increasing the heat temperatures reduced the hardness and strength but helped to improve the ductility and corrosion potential of the SLM-ed 316L stainless samples.